Calculating travel times and arrival speeds of CMEs to Earth: An analytic tool for space weather forecasting. Issue 3 (1st March 2017) - Corona‐Romero, P.; Gonzalez‐Esparza, J. A.; Perez‐Alanis, C. A.; Aguilar‐Rodriguez, E.; de‐la‐Luz, V.; Mejia‐Ambriz, J. C.
Abstract: Coronal mass ejections (CME) are one of the most important phenomena derived from solar activity that potentially perturb space weather of Earth. In this work we present a semiempirical arrival forecasting tool for Earth‐directed halo CMEs. This tool combines the piston shock model and an empirical relationship to estimate in situ arrivals of halo CMEs. The empirical relationship uses the initial conditions of CMEs to calculate the value of free parameter of the piston shock model, a parameter which is closely related to the initial inertia of CMEs. Such a value will let the model to simultaneously approximate the travel time and arrival speed of CMEs (i.e., CME arrivals). We test the forecasting capabilities of our model and its empirical relationship by calculating the arrivals of 40 halo CMEs detected during the period of 1995–2015. Our results indicate that, together, the piston shock model and its empirical relationship approximate CME arrivals with average errors of 7 h for travel times, and 100 km s −1 for arrival speeds. Our results show that our model is suitable for arrival forecasting of isolated events propagating through quiet interplanetary medium. Key Points: Arrival forecasting of CMEs Analytic modeling of CME propagation